2009
DOI: 10.1504/ijem.2009.031571
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding crisis in communication: a computer-supported training approach for emergency management

Abstract: Crisis management requires stakeholders not only to show strategic, organisational preparedness for crisis events (e.g., by systematising and professionalising coping with work), but also to develop skills in dealing with unanticipated events and other stakeholders involved in the same crisis. They should not only rely on established information flows and behaviour patterns, but also be able to deal with situational aspects. This usually involves communication work within and between organisations involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…To ensure staff have the skill necessary to communicate during an emergency, organizations will need to ensure staff are well trained. Skill development in emergency management is critical to successfully navigating emergencies, and online simulations are useful tools to accomplish this (Reuter et al , 2009). Online simulation tools are known to allow users to practise skills without serious consequence (Reuter et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure staff have the skill necessary to communicate during an emergency, organizations will need to ensure staff are well trained. Skill development in emergency management is critical to successfully navigating emergencies, and online simulations are useful tools to accomplish this (Reuter et al , 2009). Online simulation tools are known to allow users to practise skills without serious consequence (Reuter et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Skill development in emergency management is critical to successfully navigating emergencies, and online simulations are useful tools to accomplish this (Reuter et al , 2009). Online simulation tools are known to allow users to practise skills without serious consequence (Reuter et al , 2009). These simulations can be designed to teach users to sort through large amounts of information and identify messages that need to be addressed, misinformation that needs to be corrected or information that needs to be shared.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the issue has to be identified at first in order to match the single pieces of information. This can be accomplished by a simulation of possible crises (Reuter et al, 2009), which can give clues about the character and the interdependencies of required information.…”
Section: Discussion and Transferability To Other Domainsmentioning
confidence: 99%
“…Some studies in the literature have compared online, face-to-face and blended learning situations in terms of both attitude and effect on academic achievement and different results were obtained. For example, Tatlı and Ayas (2013) and Reuter et al (2009) concluded that online learning was more effective than face-to-face learning. In another study, Ferdig (2013) found no significant difference between online learning and face-to-face learning in terms of academic achievement, attitude and motivation.…”
Section: Increased Cost Lack Of Economy (1)mentioning
confidence: 99%